Quality evaluation of Coffea canephora ‘Apoatã’ seeds for rootstock production - Espíndula, Marcelo Curitiba; Botelho, Frederico José Evangelista; Clemente, Aline da Consolação Sampaio; Teixeira, Alexsandro Lara; Alves, Gleice Quele Fonseca; Oliveira, Roseane Maria Evangelista (Coffee Science - ISSN 1984-3909, 2018)
Coffea canephora ‘Apoatã’ seeds are used for the formation of rootstocks for grafting of C. arabica seedlings. The quality of seeds and the individualization of used genotypes are prevalent factors for the formation of vigorous rootstocks that will enhance the formation of quality seedlings. The aim of the present study was to characterize and evaluate the seed quality of C. canephora ‘Apoatã’ genotypes for potential use of rootstocks for C. arabica species. Were used seeds of 30 C. canephora ‘Apoatã’ genotypes, obtained from the experimental field of Embrapa Rondônia in Ouro Preto do Oeste, RO, Brazil. The seeds were processed and subjected to germination, first germination count and tetrazolium tests. Moisture, 100- seed mass and chemical composition analyses of seeds were also determined. The mass, physiological quality and chemical composition of C. canephora ‘Apoatã’ seeds vary according to the genotype. The variation of the physiological quality of C. canephora ‘Apoatã’ seeds is not related individually to caffeine, total sugars, ash, ether extract, crude fiber protein and chlorogenic acid. Seed batches of C. canephora ‘Apoatã’ from different genotypes contain seeds of different sizes, being indicated the classification before the processing stage in order to prevent mechanical damages.